STUDENTS' TEST ANXIETY: ITS SOURCES AND THEIR COPING STRATEGIES(A Study in One of Vocational Schools in Sukabumi) - Yugafiati, Rasi (2015)
This thesis reports the study on the anxiety faced by the students in one of vocational schools in Sukabumi. This study is concerned with the anxiety levels experienced by the students, the sources of their anxiety, and their strategies to reduce the anxiety. The research is mainly qualitative with some descriptive statistics which employed some data collection techniques: two questionnaires, interview, classroom observation, and document analysis. The data were analyzed by way of reducing, displaying, and interpreting data. This study reveals, first, that the students experience high anxiety in facing the final examination on English. Most of the students experience a high level of test anxiety. The second, for the test anxiety, it is found that the sources coming from people's view, preparation, procrastination, expectation, negative consequences/ negative thinking, personal problem, time pressure, format usage, students' age, students' familiarity with testing condition, testing situation factors, and not mastering the skill. The last is that the students' coping strategies are various. The coping strategies are active coping, planning, suppression of competing activities, restraint coping, seeking social support for instrumental reasons, seeking social support for emotional reasons, positive reinterpretation & grow, acceptance, turning to religion, focus on & venting of emotions, denial, behavioral disengagement, and mental disengagement. Based on the explanations above, it could be concluded that test anxiety tend to be experienced by every students which appear in a high or a low level of anxiety. Coming from various sources when facing the final examination on English, the students have their own strategies which they use to reduce the anxiety.